2009
DOI: 10.1051/medsci/2009258-9687
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrénie et toxoplasmose

Abstract: La schizophrénie est l'une des pathologies psychiatriques les plus sévères (voir [1] pour revue). Répandue dans le monde entier [2], elle atteint environ 1 % de la population adulte mondiale [3]. Elle se manifeste par une désorgani-sation de la personnalité, une altération de la perception de la réalité et des troubles cognitifs. Maladie chronique avec un impact social sévère, son étiologie n'est pas encore formellement connue. L'hypothèse neurodéveloppemen-tale suggère l'existence d'une vulnérabilité génétiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Several authors have reported a high prevalence of Toxoplasma antibodies in patients with schizophrenia, although other factors such as genetic may be present in the schizophrenia, different reports have shown that Toxoplasma is somehow associated with cases of schizophrenia. This finding justifies the need to examine the relationship between toxoplasmosis and schizophrenia with pre-clinical and clinical trials aimed to improve prevention and treatment programs in patients with psychiatric illness [71,72]. On the other hand, a meta-analysis of latent Toxoplasma gondii infection in immunocompetent hosts and cryptogenic epilepsy showed a strong association between seroprevalence rates for toxoplasmosis and prevalence rates of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a high prevalence of Toxoplasma antibodies in patients with schizophrenia, although other factors such as genetic may be present in the schizophrenia, different reports have shown that Toxoplasma is somehow associated with cases of schizophrenia. This finding justifies the need to examine the relationship between toxoplasmosis and schizophrenia with pre-clinical and clinical trials aimed to improve prevention and treatment programs in patients with psychiatric illness [71,72]. On the other hand, a meta-analysis of latent Toxoplasma gondii infection in immunocompetent hosts and cryptogenic epilepsy showed a strong association between seroprevalence rates for toxoplasmosis and prevalence rates of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several epidemiological, behavioral, and neurochemical studies suggested the existence of an association between schizophrenia and past history of infection by T. gondii (da Silva and Langoni, 2009;Dion et al, 2009;Gaskell et al, 2009;Xiao et al, 2009;Yolken et al, 2009;Zhu, 2009). …”
Section: Humansmentioning
confidence: 99%